2003
DOI: 10.1080/15428110308984848
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Exposure to Submicron Particle Mass and Number Concentrations From Manual Arc Welding of Carbon Steel

Abstract: Particle emissions from manual shielded metal arc welding of carbon steel were sampled in a typical industrial maintenance and metal fabrication workplace environment. Particle number measurements over the size range from 14 nm to 10 microm using a scanning mobility particle sizer and an optical particle counter showed that welding produced an approximately lognormal particle mode with a 120 nm count median and a geometric standard deviation of 2.07. This study produced welding particle number concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Concentrations measured in workplaces, households and urban environments can be similar or much higher Exposure to manufactured nanostructured particles in an industrial pilot plantthan the steady-state concentrations obtained at this site (Zhu et al, 2002;Stephenson et al, 2003;Maynard et al, 2004). However, as the concentrations are derived under different conditions, the outlined comparison can only provide an indication for the corresponding order of magnitude.…”
Section: Discussionmentioning
confidence: 98%
“…Concentrations measured in workplaces, households and urban environments can be similar or much higher Exposure to manufactured nanostructured particles in an industrial pilot plantthan the steady-state concentrations obtained at this site (Zhu et al, 2002;Stephenson et al, 2003;Maynard et al, 2004). However, as the concentrations are derived under different conditions, the outlined comparison can only provide an indication for the corresponding order of magnitude.…”
Section: Discussionmentioning
confidence: 98%
“…Welders' personal exposures to manganese has been measured at concentrations up to 4.93 mg/m 3 and up to 16.29 mg/m 3 for iron (Korczynski 2000;Flynn and Susi 2009), with total welding particulate levels up to 30 mg/m 3 (Susi et al 2000;Meeker et al 2007;Zeidler-Erdely et al 2012). Given that NP can represent up to 80% in number and 16% in mass of the total particles emitted during welding (Stephenson et al 2003;Dasch and D'Arcy 2008), the aerosol generated in our study is therefore representative of welder's occupational environment. This is important to consider as our experimental set-up is dedicated to expose the animals repeatedly, over long periods of time, in order to mimic a worker's lifetime occupational exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These latter NP can be produced either intentionally because of the novel properties-useful for various applications-they display (engineered NP) or generated unintentionally (during domestic activities such as cooking, smoking, incense burning, or in welding fumes) (Stephenson et al 2003;Marconi et al 2006;Ji et al 2010). Because of the rise of anthropogenic sources of NP (and particularly the engineered ones) human exposure to NP has dramatically increased in the recent years, in the general population as well as in the context of occupational exposure (Seaton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Elihn and Berg (2009) showed the ambient average PM 1 was 280 μg/m 3 during steel spot welding, in which there was good general ventilation but with other welding activities nearby. The PM 4 of 460 μg/m 3 in the breathing zone of a shielded metal arc welder has been reported by Stephenson et al (2003). More recently, a study of 215 welders showed the personally exposed median PM 4 was 1290 μg/m 3 during gas metal arc welding with solid wire, flux-cored wire, tungsten inert gas welding, and shielded metal arc welding (Lehnert et al, 2012).…”
Section: Personal Exposure Levels Of Pm 4 and Pm 01mentioning
confidence: 96%